2q-6=18

Simple and best practice solution for 2q-6=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2q-6=18 equation:


Simplifying
2q + -6 = 18

Reorder the terms:
-6 + 2q = 18

Solving
-6 + 2q = 18

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 2q = 18 + 6

Combine like terms: -6 + 6 = 0
0 + 2q = 18 + 6
2q = 18 + 6

Combine like terms: 18 + 6 = 24
2q = 24

Divide each side by '2'.
q = 12

Simplifying
q = 12

See similar equations:

| (X+3)(x^2-4x+5)= | | 2y=4y+1 | | -(5x-9y+6z)= | | f(x)=x^4+7x^3-8x-56 | | 8-t=21t-17 | | 5(x+20)=7x+20 | | X-3-1=5 | | X^2-x+304=0 | | x/--6 | | 145/170 | | -8g+2g+g=-40 | | log(base)2(2^x/3)=log(base)2(80) | | 3x^2+6=9 | | 7r-12+17r+41= | | 2x+4x=5x+4 | | 6/7(-21t)= | | 3x-4.6=0.5x+26 | | 3(x-1)-2(x-3)=2x-3 | | 4x-2(x-4)=-7+4x+2 | | 23+3h=54 | | 268=215-y | | 1/5(-10a)= | | 9a-17b+15a= | | -0.7(3a)= | | 9x-(x-1)=17 | | 4p(np-z)=0 | | 0.89x+4=1.09x | | 7x+14=2x-36 | | -4x-2.5x+11+3.6x-16.4= | | 3x-11y-6x= | | 3(x-2)=-26-7x | | 7z-1=2(4z-3) |

Equations solver categories